Coach-training in Icelandic gymnastic clubs - Sæunn Svanhvít Viggósdóttir 1980- (2020)
Training and development are essential for all organizations. The objective of this study was to examine how coach-training is implemented in Gymnastics clubs in Iceland. The research was twofold, leaders of seven clubs with 600 gymnasts and more were interviewed and asked to share their thoughts on the subject. The leaders’ definition of successful training was defined. Furthermore, the leaders were asked to explain how coach-training is conducted within their clubs. To what extent the Icelandic Gymnastic clubs are using the Icelandic Gymnastics Federations’ and the National Olympic and Sports Associations’ educational systems in coach-training. Furthermore, the leaders were asked for ideas to improve the systems. The second part of the research was a survey conducted amongst all coaches working in the same clubs as the leaders. The survey aimed to determine what the coaches consider good training methods, both within the clubs and the Icelandic Gymnastics Federations’ educational system and if their training needs are met. Finally, the thesis addresses if the coaches and leaders are in line when defining successful training. The main conclusion is that Icelandic Gymnastics Clubs use the Icelandic Gymnastics Federations’ educational system as their primary training. Most of them are using the National Olympic and Sports Associations’ educational system, but not all of them, and the main focus is not on it. All clubs have some internal training; the extent of the training varies between clubs, but mentoring, short courses, coaches’ meetings, and performance reviews were the primary training methods that are most popular. The majority of Icelandic gymnastic coaches feel that they are trained rather well in their clubs and that the Icelandic Gymnastics Federations’ educational system is working rather well, but there is room for improvement. The coaches emphasize the importance of practical training courses and think that it can improve coach-training the most. Keywords: Gymnastics, Gymnastic coaches, ...